Android application development all-in-one for dummies - Burd, Barry A. (Hoboken : John Wiley, 2012)
As a Linux-based operating system designed for mobile devices, the Android OS allows programs to run on all Android devices and appear free in the Android Market. Whether you're a beginner programmer eager to create mobile applications or you're Android-savvy and looking to submit your apps to the Android Market, this compilation of eight minibooks takes you through the ins and outs of programming for Android phones. Java expert Barry Burd walks you through Android programming basics, shares techniques for developing great Android applications, reviews Android hardware, and much more.
Book I: Android jump-start -- Book II: Android background material -- Book III: The building blocks -- Book IV: Programming cool phone features -- Book V: The job isn't done until... -- Book VI: Alternative Android develpment techniques.
"6 books in 1"--Front cover.
Includes index.
Keywords: Android (Electronic resource); Android (Electronic resource); Application software -- Development; Application software -- Design